Influence of Maternal and Paternal Parenting Style and Behavior Problems on Academic Outcomes in Primary School - Checa, Purificación; Abundis-Gutierrez, Alicia; Pérez-Dueñas, Carolina; Fernández-Parra, Antonio (Frontiers in Psychology, 2019)
Parents and teachers are concerned about the academic outcomes of children. Among the variables that play an important role in school success, parenting styles and behaviour problems are some of the most studied. Literature shows that presence of behavioral problem and parenting styles based on physical punishment, lack of consistency and ineffective limit setting are related to poor academic achievement. The present study examined the influence of maternal and paternal parenting styles and behaviour problems on the academic outcomes of primary-school children. Measures used in this study included the Inventory of Parenting Guide, the Child Behaviour Checklist and information on academic outcomes (n= 78 families). The range age of the students was 6 to 13 years old (mean= 8,08; SD= 1.6; 38 girls). The participation rate was 90,7%. The results showed that behaviour problems and sensitive parenting style were related to academic outcomes. Specifically, attentional problems and maternal sensitive parenting styles appeared to be significant predictors of academic outcomes in this study. These data suggest the relevance of attention and maternal sensitive parenting styles in understanding processes that promote academic outcomes.